Perfil lipídico en el diagnóstico de dislipidemias. departamento médico odontológico de la Universidad Nacional de Chimborazo. mayo 2017-junio 2018 - Quito Pinta, Jimmy Javier (2018)
The dyslipidemia are disorders of lipoprotein metabolism, including overproduction or deficiency. It is a chronic disease that increases the risk of cardiovascular disease, due to the asymptomatic nature of dyslipidemia in the presence of signs or symptoms of cardiovascular disease development, for its identification and evaluation is required. The aim of interpreting the results of lipid profile tests and the diagnosis of dyslipidemias of users who were treated at the Clinical Laboratory of the Department of Dentistry of the National University of Chimborazo in the period May 2017-June 2018, together with the medical records in order to determine the relationship between the laboratory results and the clinical data of each patient; it was started taking into account that it is a descriptive investigation since results of tests of the lipid profile, Body Mass Index (BMI), gender and age were collected. The study is conducted by several risk factors that students, teachers and administrative staff are prone to: smoking, alcoholism, poor diet and sedentary lifestyle. These last two could be for long days of work. Emphasizing bad eating habits, a large percentage of foods ingested in the institution are high in saturated fats and do not have adequate nutritional power. As a result, a value of 23.99Kg / m2 was obtained as average BMI, the largest number of patients belonged to the group of 20 to 35 years (36%) and the male gender prevailed with 26 (50%) patient, 26 (50 %) of the female gender. The prevalence of dyslipidemia was present in 52 (61%) patients followed by presumptive diagnosis, which reflected a figure of 16 (19%) patients attended.